Research Trends on Students Engagement in EFL Classroom: A Literature Analysis on Online Scientific Publication from 2020-2023 - Saleh, Yuwin Rustam; Darwis, Nirwana (English Education Department, 2024)
This bibliometric analysis examines research trends on students’ engagement in EFL classrooms from 2020 to 2023, revealing substantial academic interest with a total of 982 publications. The analysis highlights a peak in publications in 2022, underscoring the growing emphasis on student-centered teaching approaches. However, citation metrics show a significant decline over the years, indicating a shift in scholarly attention and citation behavior. The study also identifies a marked disparity in author influence, with the top 20 authors contributing to a significant portion of the citations. Keyword analysis and network visualization using VOSviewer reveal a strong focus on themes like online learning, student engagement, and the impact of the COVID-19 pandemic. These findings suggest that while the field is expanding, there is a need for ongoing research to address emerging challenges and sustain academic impact. This study contributes to understanding the dynamic landscape of EFL education, providing insights for future research and practice.